Agroecological TRANSITIONS for our future - TRANSITIONS Program; Ricci, Fabio; Araujo De Lima, Silvia; Shelton, Sadie; Geck, Matthias; Wollenberg, Eva Karoline; Mockshell, Jonathan; Crossland, Mary (2025)
This infographic was produced by the 3 projects' managers and communication officers of the TRANSITIONS Program (Agroecological transition programme for building resilient and inclusive agricultural food systems) funded by the European Union and managed by IFAD. The TRANSITIONS program aims to identify, test and scale up highly effective catalyzers of agroecology-driven food system transformation by means of three key actions: Agroecological transitions are complex and can take multiple pathways! We can view them as a subway network... different stations and lines leading toward a UNIFIED GOAL: sustainable, resilient and healthy food, and agricultural systems. Follow the different lines to see where the TRANSITIONS program works and how it aims to foster agroecological conversion through specific milestones! 1. The development and implementation of holistic performance metrics for agriculture across scales 2. Inclusive digital resources to support climate resilient agroecological transitions 3. Innovative pathways for long-term incentives and private and public investment